2003
DOI: 10.1093/pcp/pcg146
|View full text |Cite
|
Sign up to set email alerts
|

Lotus japonicus: A New Model to Study Root-Parasitic Nematodes

Abstract: ;Sedentary plant-parasitic nematodes engage in complex interactions, and induce specialized feeding structures by redirecting plant developmental pathways, and parallels have been observed with rhizobial nodule development on legumes. A model legume would greatly facilitate a better understanding of the differences between parasitic (nematode) and mutualistic (rhizobia and mycorrhizae) symbioses, and we have developed Lotus japonicus as such a model. Conditions for efficient parasitism by root-knot nematode (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 38 publications
1
43
2
Order By: Relevance
“…Strikingly, ET has been suggested to be critical for syncytia formation during cyst nematode infections on Arabidopsis (Goverse et al, 2000;Wubben et al, 2001). However, for RKN, Lohar and Bird (2003) found no changes in susceptibility in ET-resistant Lotus japonicus, and the fact that ET was not detected in galls at 1 to 2 d post infection (Glazer et al, 1983) in combination with the transcriptional patterns observed in this study and by Barcala et al (2010) argue against a crucial role for ET-activated pathways during early giant cell differentiation; rather, they suggest that the RKN is actively suppressing the ET pathway and other defense signaling pathways in the root. The contrasting roles of ET in RKN and cyst nematode infection might be explained by their different modes of action, as RKN migrate in a stealthy way between the root cells whereas cyst nematodes move through them, causing extensive necrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strikingly, ET has been suggested to be critical for syncytia formation during cyst nematode infections on Arabidopsis (Goverse et al, 2000;Wubben et al, 2001). However, for RKN, Lohar and Bird (2003) found no changes in susceptibility in ET-resistant Lotus japonicus, and the fact that ET was not detected in galls at 1 to 2 d post infection (Glazer et al, 1983) in combination with the transcriptional patterns observed in this study and by Barcala et al (2010) argue against a crucial role for ET-activated pathways during early giant cell differentiation; rather, they suggest that the RKN is actively suppressing the ET pathway and other defense signaling pathways in the root. The contrasting roles of ET in RKN and cyst nematode infection might be explained by their different modes of action, as RKN migrate in a stealthy way between the root cells whereas cyst nematodes move through them, causing extensive necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some papers have shown the importance of SA in plant defense against RKN (Owen et al, 2002;Nandi et al, 2003;Branch et al, 2004) and cyst nematodes (Wubben et al, 2008), but Bhattarai et al (2008) suggested that low levels of SA are already sufficient for tomato (Solanum lycopersicum) basal resistance to RKN. Concerning the JA/ET pathways, Lohar and Bird (2003) did not see changes in susceptibility in ETresistant Lotus japonicus plants, but foliar JA application was shown to induce systemic defense against RKN in tomato (Cooper et al, 2005). Again contradicting this observation, Bhattarai et al (2008) found that an intact JA signaling pathway is required for tomato susceptibility to RKN.…”
mentioning
confidence: 88%
“…A possible connection between AON and defense signaling is supported by the fact that several autoregulation mutants are hypersusceptible to nematode and pathogen infection (Lohar and Bird 2003;Tazawa et al 2007). In line with this, Kinkema and Gresshoff (2008) reported that, in soybean, a subset of defenserelated genes is regulated via the AON receptor GmNARK, albeit in a nodulation-independent manner.…”
Section: Modulation Of Host Immunity In Nonsymbiotic Beneficial Intermentioning
confidence: 99%
“…Interestingly, the Lotus japonicus HAR1 gene encodes a Leu-rich repeat (LRR) receptor-like kinase with the highest level of similarity to the Arabidopsis CLAVATA1 gene (Krusell et al, 2002;Nishimura et al, 2002). The har-1 mutant displays a hypernodulating phenotype and was recently reported to be hyperinfected by root-knot nematodes (Lohar and Bird, 2003), implicating the involvement of the CLAVATA pathway in both rhizobia and nematode-plant interactions. In addition to potential nematode-secreted CLE ligand mimics, a NodL ortholog was recently identified among expressed sequence tags of the root-knot nematode (McCarter et al, 2003), and initial evidence suggests that signals from infective juveniles of root-knot nematodes can have similar effects as Nod factor on developing root hairs of the legume model L. japonicus (Weerasinghe et al, 2005).…”
Section: Nematode Parasitism Genesmentioning
confidence: 99%